Maternal-fetal and neonatal characteristics associated with Kangaroo-Mother Care Method adherence - Patrícia de Padua Andrade Campanha; Maria Clara de Magalhães-Barbosa; Gustavo Rodrigues-Santos; Arnaldo Prata-Barbosa; Antônio José Ledo Alves da Cunha (Elsevier, 2023)
Objective: To describe the association of maternal and neonatal characteristics with the adherence status to the in-hospital stages of the Kangaroo-Mother Care Method - KMC (full, partial, and no-adherence). Methods: Retrospective cohort study including infants < 2500 g admitted to a reference maternity hospital for the KMC in Rio de Janeiro from January to December 2018. Maternal and neonatal characteristics were distributed according to the adherence status to the KMC in-hospital stages. In the first stage, KMC is performed in Neonatal Intensive Care Unit and Conventional Neonatal Intermediate Care Unit. The second stage is completed in Kangaroo Neonatal Intermediate Care Unit. Multinomial multiple regression was performed with KMC adherence as a three-category dependent variable and maternal and neonatal characteristics as independent variables. Results: Of 166 dyads, 102 (61.5%) participated in two stages. Those who did not participate in any stage (n = 52; 31.3%) had a lower level of education, a higher frequency of adverse conditions, and were more often single mothers; mothers who participated only in the first stage (n = 12; 7,2%) had more premature and sick infants. Conditions associated with adherence to the two stages compared to no adherence were: high school education (OR = 2.34; 95% CI = 1.08-5.07), presence of a partner (OR = 3.82; 95% CI = 1.7-8.61), no adverse conditions (OR = 3.54; 95% CI = 1.59-7.89) and no neonatal resuscitation (OR = 2.73; 95% CI = 1.22-6.1). Conclusions: The study identified maternal and neonatal conditions associated with adherence status to the KMC. The results suggest opportunities to improve adherence.